Multimodality imaging of bone marrow involvement in paediatric oncology - Rutger A.J. Nievelstein; Lise Borgwardt; Thekla von Kalle; Annemieke S. Littooij; Lil-Sofie Ording Müller; Nelleke Tolboom (EJC Paediatric Oncology)
Identifying bone marrow involvement (with or without bone destruction) in children with cancer is essential for adequate diagnosis, prognostication, therapy planning, and response assessment. Imaging plays an increasing role, with MRI including DWI and [18F]FDG-PET/CT as the most commonly used imaging techniques. Interpretation of the paediatric bone marrow on imaging might be challenging because of age-related physiological changes in the bone marrow, as well as disease and therapy related effects. In this review, we discuss how the imaging techniques available may be employed to detect bone marrow involvement (BMI) in paediatric oncology. Furthermore, insights into physiological, disease and therapy related bone marrow changes in children that might influence bone marrow imaging interpretation will be provided.